(untitled) (Fiep Bulletin - online, 2012)
The quality of life of elderly people has attracted attention of many researchers. Identify how is the quality of life ofolder project participants, through the quality of life questionnaire SF-36 is the objective of this study. The methodology used is adescriptive, where the data came from the SF-36 were administered to 60 elderly projects and Dance Senior Ballroom Dance ofUNATI-UNISUAM. The conclusion of this research is that the elderly participants of the project despite having bad social aspectsbut have a good quality of life.